Study on the Dynamic Performance of Locally Resonant Plates with Elastic Unit Cell Edges. (7th June 2021) - Sun, Yonggan
Abstract : A Floquet–Bloch approach is employed to demonstrate the stop bands for an infinite locally resonant plate. In addition, the effects of the connection stiffness of the unit cells on the band gap and dynamic performance of a locally resonant plate are analysed. The results show that the degree of inhibition of elastic waves in the band gaps increases rapidly when the connection stiffness of the unit cells increases within the scope of the transition stage stiffness. However, outside of the range of transition stage stiffness, the degree of inhibition of elastic waves in the band gaps basically remains unchanged. This discovery widens the application scope for vibration and noise control using locally resonant plates.